DNA, spectroscopic and geochemical analyses of bone fragments and associated speleothems in Postojna cave, Slovenia - Lipar, Matej (Acta carsologica, 2020)
Loose bone fragments coated with calcite precipitate including a loose/broken stalagmite containing small fragments of ce - mented bones were collected from the Postojna Cave to investi - gate whether deoxyribonucleic acid (DNA) can be determined. The study is complemented by the Fourier-transform infrared spectroscopy - attenuated total reflectance (FTIR-ATR) analy - sis in order to determine the alteration of the bones and to test whether this analysis can be used as an indicator of possible DNA preservation. In addition, geochemical analyses were conducted in order to determine whether the associated flow - stone/stalagmite is suitable for elucidating the timing of bone thanatocoenosis and further palaeoenvironmental analyses. The organic matter (collagen) is poorly preserved. However, we succeeded in amplifying a 94 bp long fragment of the cytochrome b (Cyt b) gene of mitochondrial DNA (mtDNA) in polymerase chain reaction (PCR) for one sample, and in sequencing the amplified products. The 70 bp long sequence obtained corresponds to that of the Cyt b of the cave bear ( Ursus deningeri or Ursus spe - laeus sensu lato ). The uranium-thorium dating of the speleothem covering the bones revealed its thanatocoenosis occurred prior to 55 ka, most likely in the late marine isotope stage 4 or early marine isotope stage 3. High porosity and recrystallisation of the flowstone/stalagmite at this part of the cave prevent high-reso - lution palaeoclimatic interpretation; however, low-resolution stable isotope geochemistry suggests a steppe-like environment during the subsequent growth of the speleothem.
Keywords: deoksiribonukleinska kislina; deoxyribonucleic acid; palaeoclimate; paleoklima; stalagmit; stalagmite